Developing a Biodiversity Assessment Tool to Enable the Integration of Biodiversity into Sustainable Building Practice: The New Zealand Biodiversity Factor—Building (NZBF-B) - Theis, Jacqueline; Pedersen Zari, Maibritt; Shanahan, Danielle; Freeman, Claire; van Heezik, Yolanda (MDPI AG, 2026)
Sustainable building practices can reduce environmental harm and support resilient urban development. To aid built-environment professionals such as architects, building scientists and planners in accomplishing regenerative design objectives, a variety of building rating and accreditation schemes have been developed, such as Greenstar or the Living Building Challenge. These schemes primarily focus on sustainability targets, such as energy and water use. Biodiversity considerations, despite their importance for ecosystem services and human health, are predominantly absent as core objectives in the building rating tools currently in use. To address this gap, we introduce the New Zealand Biodiversity Factor—Building (NZBF-B), a tool created to educate and incentivise the integration of biodiversity into buildings by assessing their biodiversity value, with a focus on prioritising native species. We outline the development of the NZBF-B, including its components, its scoring methodology, and an expert-informed weighting process used to determine the ecological relevance of each category. The tool captures key characteristics of building-associated biodiversity through measurable indicators that reflect both habitat provision and opportunities to strengthen human–nature connection. We advocate for the use of the NZBF-B alongside existing certification schemes to achieve more effective green building performance outcomes related to biodiversity.
Keywords: 33 Built Environment and Design; 3301 Architecture; 4104 Environmental Management; 41 Environmental Sciences; Generic health relevance; 11 Sustainable Cities and Communities; 15 Life on Land; 12 Built Environment and Design; biodiversity assessment; building; sustainable building rating systems; urban vegetation; accreditation